2003
DOI: 10.1002/cne.10913
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic acetylcholine receptor distribution in relation to spinal neurotransmission pathways

Abstract: Neuronal nicotinic receptors (nAChR) are pentameric assemblies of subunits of a gene family where specified combinations of alpha and beta subunits form functional receptors. To extend our understanding of the role of spinal nAChR in the processing of sensory stimuli and regulation of autonomic and motor responses, we initiated investigations to localize nAChR subunit expression within discrete spinal regions and cell types. High-affinity epibatidine binding was present in the superficial dorsal and ventral ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 52 publications
(68 reference statements)
3
58
0
Order By: Relevance
“…It was therefore suggested that Vc1.1 might produce pain relief via inhibition of 3-and/or 5-containing nAChRs on sensory nerves. α3, α4, α5, β2 and β4 subunit transcripts are all found in spinal cord parenchyma and sensory ganglia (Khan et al 2003). Although the specificity of nAChR antibodies has been questioned (Moser et al 2007), the subunits all appear to be expressed on primary afferents that co-label immunohistochemically with IB4, and with synaptophysin in superficial dorsal horn (Khan et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was therefore suggested that Vc1.1 might produce pain relief via inhibition of 3-and/or 5-containing nAChRs on sensory nerves. α3, α4, α5, β2 and β4 subunit transcripts are all found in spinal cord parenchyma and sensory ganglia (Khan et al 2003). Although the specificity of nAChR antibodies has been questioned (Moser et al 2007), the subunits all appear to be expressed on primary afferents that co-label immunohistochemically with IB4, and with synaptophysin in superficial dorsal horn (Khan et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…α3, α4, α5, β2 and β4 subunit transcripts are all found in spinal cord parenchyma and sensory ganglia (Khan et al 2003). Although the specificity of nAChR antibodies has been questioned (Moser et al 2007), the subunits all appear to be expressed on primary afferents that co-label immunohistochemically with IB4, and with synaptophysin in superficial dorsal horn (Khan et al 2003). It therefore remains possible that pain relief may be achieved after intrathecal administration by antagonism of nAChRs comprising complex combinations of α3 with α5, β4 and β2 subunits, perhaps in combination with other less common subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Other complicating factors are that, in the presence of bicuculline, the depression was not only counteracted but replaced by excitation (possibly by unmasking an excitatory pathway) and that bicuculline might also reduce the test responses. The latter effect suggests that it might also interact with an excitatory receptor, such as the nicotinic acetylcholine receptor possibly found on primary afferents (Ninkovic and Hunt, 1983;Khan et al, 2003) and known to be blocked by bicuculline (Demuro et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Bovine adrenal chromaffin cells express ␣3-, ␣5-, ␣7-, and ␤4-nAChR subunits (Sala et al, 2008). Accordingly, the main nAChR subtypes expressed on nociceptive peripheral fibers and their central terminations are composed of ␣3, ␣5, ␤4, and ␤2 subunits (Khan et al, 2003;Lang et al, 2003;Rau et al, 2005). Vc1.1 also inhibited peripheral nerve-mediated vascular responses in rats (Satkunanathan et al, 2005) and, at low concentrations (100 nM), inhibited excitatory responses of Sandall et al, 2003;Satkunanathan et al, 2005;Vincler et al, 2006;Klimis et al, 2011 CyclizedVc1.1 Partially reverses mechanical allodynia in several neuropathic models after oral dosing.…”
Section: E Ligand-gated Ion Channels Inhibitors In Pain Managementmentioning
confidence: 99%